Konsep dan pengertian ‘Penyakit Pekerjaan’: isu-isu perundangan - Che Thalbi Md. Ismail,; Kamal Halili Hassan, (Fakulti Undang - Undang, 2009)
Compared to ‘accident cases’, the attention to ‘occupational disease’ was not very much given in the field of industrial safety. In many instances, ‘disease’ cases were regarded as part of ‘accident’ cases. As such, the disease cases were included as part of the accidents statistics used in this country. The formal statistics shows that disease cases form only a small part of the overall claims. The rest are cases of accidents at the workplace or commuting accidents. Therefore, a question arose whether a rigid interpretation is given to the term ‘occupational disease’ similar to the meaning of accidents. Does that result in the small number of claims made by insurers? Further, how can we give a better opportunity for them to succeed in claims for occupational diseases? Should a separate platform be made available to ‘disease’ and ‘accident’ claims in order to give a better chance to succeed in disease claims? Are the claims permitted for the diseases listed in the Act only?